Controlling the reaction network of Ni/silica derived conversion of bio-oil surrogate guaiacol - Nils Kretzschmar; Oliver Busse; Markus Seifert (Carbon Resources Conversion, 2024)
Replacing fossil carbon sources with green bio-oils is a promising route to switch to a sustainable chemical industry, although their high oxygen contents are challenging. Catalytic hydrodeoxygenation is a favored route to upgrade bio-oils to renewable fuels and basic chemicals. In this work, we investigated Ni/SiO2 catalysts with differing metal dispersity in continuous mode conversion of guaiacol with a statistical experimental design for 250 °C to 400 °C, 2 h up to 5 h time on stream (ToS) and subsequently different residence time besides other parameters. While low temperature (250 °C) promotes cyclohexanol formation from guaiacol, high temperature (400 °C) inhibits hydrogenation, leading to phenol and methane. For medium temperature (340 °C), the selectivity for cyclohexanone increases. Cyclohexanol and cyclohexanone (KA-oil) are the industrial basis for polyamide 6. Furthermore, we clarified the role of 2-methoxycyclohexanol (2MC) in the reaction network towards KA-oil for continuous-mode operation. Statistical analysis was used to predict and optimize product selectivity and yield, leading to the best yield of cyclohexanone/-ol at 327.5 °C, low ToS, medium residence time, high particle dispersity, and medium hydrogen pressure (15 bar(g)).